The Impact of Presence or Absence of Father on Daughters’ Marital Relationship: Pakistani Perspective - Shahzad, Maham (JSSH, 2026)
This research explores how the presence or absence of father impacts daughters’ marital relationship, how daughters with absent father view men, what qualities they idealize and how they cope and adjust with the situations they face with their spouse and what are the perceptions of daughters whose father is present. While previous research has largely concentrated on the effects of father absence or presence on daughters' self-esteem, developmental outcomes, sexual behaviour, and changing parental roles, limited data exist on how both father absence and presence shape daughters' views of men and their ideas of spousal relationships. The present study includes the sample of fifteen daughter who voluntarily participated in the research. The results suggest that fathers, whether present or absent, have a great influence on daughters’ perception about men and based on those ideas how they choose their partners. It explains the factors which are related to the absence and presence of father during childhood that could stay with individuals as they grow up. Most daughter showed a fear of getting attached and getting hurt but at the same time they praised their husband’s affection and support towards them. Whereas, daughter who reported a positive and consistent presence of father explained great trust in men, clear expectations of mutual respect, and a strong sense of emotional security within their marriages. The findings further explained that the early relational pattern with fathers, either characterized by absence and inconsistency or presence and support, can persist into adulthood and shape marital adjustment. The biggest implication of the study falls for the multicultural perspective because different cultures have different values and belief systems and their relationship emerged differently with fathers. It could also serve as a help to single mothers to induce the idea that how to shape their daughters’ ideals by becoming an example of a healthy marital relationship.